ANALISIS FRAMING DETIK.COM DALAM PEMBERITAAN ADZAN DI MEDIA PERANCIS AGENCY FRANCE PRESSE - Viky Ardinza; Galih Akbar Prabowo (QAULAN: Journal of Islamic Communication, 2024)
This study examines five news published by the online media Detik.com about the news of the French foreign media Agency France Presse (AFP), which highlights the call to prayer in Indonesia by uploading a news entitled "Piety or Noise Nuisance? Indonesia Tackles Call to Prayer Volume Backlash”. The purpose of this study is to find out how Detik.com framed its five stories with four elements of Robert Entman's framing, namely the Define problem aspect, the Diagnose Cause aspect, the Make Moral Judgment aspect, and the Treatment Recommendation aspect. This research includes the type of Framing Analysis research using a qualitative approach, Data collection using non-participant observation and documentation. Data analysis techniques using Robert Entman's model of framing analysis with four aspects of Define problem, aspects of Diagnosis Cause, aspects of Make Moral Judgment, and aspects of Treatment Recommendation. The results of this study are seen from the framing element Define problem, Detik.com media tries to define the problems that occur about French foreign media reporting Agency France Presse (AFP). Diagnose Causes, Framing developed by Detik.com in five news stories, namely mentioning the source of the problems that are currently happening, causing polemics in the community, namely the news from the French foreign media Agency France Presse (AFP), highlighting the call to prayer in Indonesia. Make Moral Judgment, it can be seen that Detik.com media is trying to display moral values that refute the AFP media coverage. Detik.com's Treatment Recommendation media emphasizes solving existing problems.